Mental health help-seeking intention among health workforce in pahang: validation of mbace, barriers, associated factors, and the development of psyhelp pocket guide - Kunyahamu, Muhammad Syafiq (2024)
Introduction: The health workforce’s mental well-being is crucial for healthcare systems’ sustainability. While it is recognised that the health workforce are exposed to high-stress and demanding situations due to the nature of their roles, some of them do not seek professional help when facing mental health challenges. Although the importance of ensuring that these individuals receive adequate mental health support is evident, numerous factors influence their decisions in seeking professional help. This intricate interplay requires a comprehensive examination, not just to inform effective strategies and interventions but also to foster a deeper understanding of the underlying complexities. Objectives: The primary aims were to: (1) translate, adapt, and validate the Barriers to Access to Care Evaluation (BACE-3) questionnaire for the Malay-speaking population, (2) determine the mental health help-seeking intention score, barriers, and associated factors among the health workforce in Pahang, and (3) develop the PsyHELP pocket guide to encourage the health workforce to seek help from mental health professionals. Methodology: The research was conducted in three phases. Phase 1 involved a detailed process of translating and adapting the BACE-3 questionnaire into the Malay version (MBACE). This version was then validated using Confirmatory Factor Analysis (CFA) in a cross-sectional study with 188 participants from diverse health workforce categories. The second phase employed a cross-sectional study design, utilising a set of self-administered questionnaires with 470 participants to gauge mental health help-seeking intentions, perceived barriers, and their associated factors. In the third phase, the PsyHELP pocket guide was developed, grounded in the Health Belief Model. This guide serves as an educational tool tailored specifically for the health workforce, aimed at bolstering mental health help-seeking behaviours. Results: The 28-item MBACE questionnaire was proven as a reliable and valid tool for the Malay-speaking health workforce, with Cronbach’s alpha values between 0.92 and 0.94. In Phase 2, the mean mental health help-seeking intention score was noted at 4.9 (SD=1.2). Significant factors associated with this intention were ‘perceived need for help’ (B = 0.532, p < 0.001) and ‘perceived stigma barriers’ (B = -0.588, p < 0.001). In the final phase, the PsyHELP pocket guide was introduced, incorporating insights from the earlier phases and presenting a practical resource for the health workforce. This guide integrates comprehensive mental health concepts and strategies tailored to the health workforce, highlights the importance of professional help, aims to mitigate stigma, and offers actionable steps towards achieving mental well-being. Conclusion: This comprehensive study underscores the complexities of mental health help-seeking behaviours among the health workforce in Pahang. It gives more insights into the mental health help-seeking intention score, as well as the barriers and associated factors within the Malaysian health workforce, highlighting the roles of perceived need for help and perceived stigma-related barriers that are significantly associated with professional mental health help-seeking intention. The validated MBACE questionnaire offers an effective tool to assess barriers, while the PsyHELP pocket guide emerges as a beacon for the health workforce to navigate their mental well-being. While PsyHELP looks like a promising intervention, its full potential and impact require further validation and research.